Performance of a Lever‐Gear Type Piezoelectric Energy Harvester for Collecting Pedestrian Energy. Issue 4 (13th February 2022) - Cai, Yuan; Liao, Peng; Ma, Wenyong; Fu, Jiyang; He, Yuncheng
Abstract : As pedestrian‐induced energy exists widely in our daily life, the collection of pedestrian energy has attracted increasing attention. Herein, a novel energy harvester is developed to capture the kinetic energy of pedestrians. The mechanical part of the energy harvester mainly consists of a lever structure and a gear transmission component, which is used to convert the kinetic energy of pedestrians into that associated with the rotation of the device. Energy is collected by a polyvinylidene fluoride (PVDF) piezoelectric film. The performance of the harvester is tested under both indoor and outdoor conditions. Experimental results show that the maximum output voltage of the harvester with a single PVDF film is 1170 mV, and the harvester reaches the best output state when the load is 510 kΩ (acceleration 0.3 g (1 g = 9.8 m s −2 ), frequency 5 Hz) with the maximum output power equal to 1.41 μW. The harvester is then optimized by adding more PVDF films, and the improved device is found to possess a higher working efficiency, with the output voltage and power increased by 58.6% and 26%, respectively. Finally, outdoor tests are conducted, and the results further confirm the feasibility of using the device to harvest the ultralow frequency kinetic energy of pedestrians. Abstract : A piezoelectric energy harvester is proposed to collect the kinetic energy of pedestrians. The harvester involves a gear–lever mechanism, which is used to amplify the amplitude and frequency of the input vibration source. Both indoor and outdoor experiments are carried out to examine the working performance of the device.